QUANTITY OF PRECIPITATION REACHING Pinus brutia AND Pistacia khinjuk STANDS IN THE AKRA REGION (Mesopotamia Journal of Agriculture)
This study was conducted at Akra region ( 36.75° N and 43.88° E) northern Iraq, during 2006 – 2007 water year. The elevation of study area is approximately 766 m above sea level. The average annual precipitation is 720.46 mm and the mean annual temperature is 18.1˚ C. Interception loss was calculated by measuring gross rainfall, throughfall and stemflow in two forest stands, the first is pine ( Pinus brutia Ten.) plantation 800 trees per hectare at 28 years old, and the second is Terebinth (Pistacia khinjuk Stock.) plantaion, 950 trees per hectare, at 18 years old. Gross rainfall was measured by using five rain gauges (12.5cm) in diameter and one rain gauge recorder (CASELLA). Throughfall was measured by using 18 rain gauges of (12.5cm) diameter distributed randomly under the canopy of each stand. The stemflow was measured from eight trees selected randomly within each stand. The result indicated that the amount of Throughfall , stemflow and interception in pine and Terebinth stand were ( 63.31 , 0.34 , 36.35) and (83.55 , 2.36 , 14.09) percent of gross rainfall (780.22 mm) respectively. Regression equations were carried out between rainfall as independent variable and throughfall, stemflow and interception as dependent variables. The study involved the chemistry of precipitation, throughfall and stemflow, The result showed that the concentration of cations and anions increased after the rainfall passed through the canopy and flowed via the bole, the sequence of total cations and anions concentration decreased in the order of: stemflow < throughfall < rainfall.